1994
DOI: 10.1002/gcc.2870110305
|View full text |Cite
|
Sign up to set email alerts
|

Aneusomy of chromosomes 7 and 17 detected by fish in prostate cancer and the effects of selection in vitro

Abstract: Twenty prostate tumor specimens, obtained from radical prostatectomies, and two lymph node metastases were examined by classical and molecular cytogenetic methods. A sample from each tumor was analyzed histologically and used for touch preparations. Adjacent samples were used for preparation of single-cell suspensions before cell culture (DirFISH) and for establishing cell cultures, which were subsequently harvested for classical G-banding analysis. Fluorescence in situ hybridization (FISH) was performed on to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…We had found a preferential growth of diploid cells with loss of the aneuploid cell populations either immediately after cell culture initiation or early during progressive subcultivation. Similar observations were reported by other groups [5,6,13,14].…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…We had found a preferential growth of diploid cells with loss of the aneuploid cell populations either immediately after cell culture initiation or early during progressive subcultivation. Similar observations were reported by other groups [5,6,13,14].…”
Section: Introductionsupporting
confidence: 82%
“…Only actively growing cells can be analyzed by standard cytogenetic studies. The majority of cell cultures derived from prostatic carcinomas have a low proliferation and exhibit a normal karyotype with chromosomal changes in less than 25% of all cases [13,27]. In contrast, DNA aneuploidy seems to be a more frequent event in prostatic adenocarcinomas when interphase cytogenetic analysis (FISH) was performed [10].…”
Section: Cell Outgrowth and Morphology In Co-culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies suggested that f75% of prostate cancer tumors had normal male karyotypes; however, there is now evidence by subsequent analysis over cell culture times that normal cells seem to be selected for in vitro (4,5); therefore, growth of tumor cells was not ideal. Several candidate chromosomes have been suggested as playing a role in the development of prostate cancer, among which are chromosomes 1,7,8,10,17, and X (6-10).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) has been applied to the study of various solid tumors (Hopman et al, 1991;Jones et al, 1994;Wada et al, 1997), mainly for the detection of numerical chromosome aberrations by using centromeric probes. There have been very few reports of FISH studies on PTCs, namely, a characterization of a chromosome structural anomaly in the cell line TPC1 (Jossart et al, 1995(Jossart et al, , 1996 and a similar study in a PTC case (Lehmann et al, 1997).…”
Section: Copyright © 2000 S Karger Ag Baselmentioning
confidence: 99%